On Generalized Regularized Trace of a Fourth-Order Differential Operator with Operator Coefficient - Aslanova, N. M.; Bairamogly, M. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We deduce a formula for the trace of a boundary-value problem with unbounded operator coefficient and boundary conditions depending on the parameter.